Impact of chitosan modification on the material properties of acrylic resin base - Al-Takai, Ihssan F.; Al-Nema , Luma; Jabrail, Fawzi H. (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: 3D-printed polymethyl methacrylate is a light-cured commercial resin used in the 3D printing sector due to its affordability, good adaptability, minimal odor, and low irritation. Purpose: To investigate the impact of modified chitosan on the surface hardness and flexural strength of printed dental resin. Methods: A modified chitosan solution was cross-linked with adipic acid at concentrations of 0.1, 0.05, and 0.01 wt.% and then added to 3D-printable acrylic resin at 2, 5, and 10 wt.%. After addition, samples were prepared to test surface hardness and flexural strength. A total of 100 specimens were used in the research, grouped into 10 sets. Five specimens were prepared for each additive percentage, and five specimens served as a control group (3D-printable resin without modification) for each test. Results: The results showed that the (adipic acid/chitosan) 0.1/2 wt.% group had the highest flexural strength (134.370 MPa) and surface hardness (32.46 VHN), while the lowest flexural strength (49.198 MPa) and surface hardness (21.22 VHN) were observed in the (adipic acid/chitosan) 0.01/10 wt.% group. Conclusion: Modification of chitosan with adipic acid positively influences the flexural strength and surface hardness of 3D-printed denture bases. However, increasing the chitosan content beyond 2 wt.% reduces both surface hardness and flexural strength in modified 3D-printed polymers.